(untitled) (Development Service Industry Management, 2025)
The article discusses the relevance of inclusiveness in the modern hospitality industry, which is not only a social obligation but also an important factor in sustainable development. The author emphasizes global trends in creating a barrier-free environment and an inclusive approach, as well as the active development of this area in Ukraine. The main challenges faced by enterprises in the industry in implementing inclusive practices are analyzed, including financial constraints, insufficient staff training, uneven infrastructure development, lack of awareness of inclusiveness, legal and regulatory requirements, stereotypes and social stigma, problems of technology adaptation, market competition, lack of sufficient experience and best practices, as well as cultural and social barriers. A model for addressing these challenges is proposed, which includes a number of measures and initiatives aimed at overcoming key barriers and creating conditions for the successful implementation of inclusive practices in the hospitality industry. Specific recommendations for travel agents to increase the level of inclusiveness of their services, including website adaptation, staff training, office adaptation, offering inclusive tours and services, and cooperation with public organizations, are considered. The author outlines the prospects for the development of inclusiveness in tourism and hospitality, taking into account the achievements of science and technology, including the development of barrier-free infrastructure, the use of modern technologies, staff development, expanding the range of inclusive tourism services, cooperation between various stakeholders and raising public awareness. The importance of an integrated and systematic approach to the implementation of inclusive practices in the hospitality industry is emphasized, as well as the need for further research in this area to create a more inclusive and just society where everyone has equal opportunities to receive quality and affordable services.